Tracheal rupture caused by fall from a height - Hızarcı, Burcu; Erdoğan, Cem; Öz, Hüseyin (ENT Updates, 2016)
Follow-up and treatment of multiple lesions in intensive care units are arranged within the discipline of approach to a case of injury. Herein, we present a 38-year-old female patient who had head trauma caused by a fall from a minibus. The patient was presented to our intensive care unit with epidural hematoma; however, tracheal rupture was found during the follow-up. Tracheal injuries and especially ruptures are not frequently encountered events even in cases with severe traumas. In traumatic events, it is difficult to diagnose tracheal rupture because of serious problems related with many organ systems. After establishment of diagnosis, it is possible to encounter relevant neurological and infectious problems because of longer treatment process. As in the case with our patient, in patients without any additional previously experienced respiratory problems while intubated development of respiratory distress hours after recurrent periods of intubation and extubation should suggest the presence of tracheal rupture.